2016
DOI: 10.1111/str.12186
|View full text |Cite
|
Sign up to set email alerts
|

Shear Band Evolution in Polymer Bonded Explosives Subjected to Punch Loading

Abstract: The shear band development and potential hot-spot initiation of polymer-bonded explosive were investigated under low-rate punch loading and combined punch and thermal loading. The digital image correlation method was used for deformation analysis. The obtained results showed that the initiation and development of shear bands at room temperature occur in three stages and demonstrated that the material suffers a prolonged shear stress concentration in a local area. Large shear was shown to lead to the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The results showed that a dead zone forms in the strain field immediately under the punch in agreement with the slip-line solution of the punch problem. Liu et al [22] investigated shear band development and potential hot-spot initiation in PBXs using a punch-loading experiment at different temperatures. At room temperature, initiation and development of shear bands occurred in three stages and the material suffered a prolonged concentration of shear stress in one area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that a dead zone forms in the strain field immediately under the punch in agreement with the slip-line solution of the punch problem. Liu et al [22] investigated shear band development and potential hot-spot initiation in PBXs using a punch-loading experiment at different temperatures. At room temperature, initiation and development of shear bands occurred in three stages and the material suffered a prolonged concentration of shear stress in one area.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . [22] investigated shear band development and potential hot‐spot initiation in PBXs using a punch‐loading experiment at different temperatures. At room temperature, initiation and development of shear bands occurred in three stages and the material suffered a prolonged concentration of shear stress in one area.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the DIC method has been used to investigate various mechanical parameters (e.g., Young's modulus, Poisson's ratio, stress intensity factor, residual stress, and thermal expansion coefficient) of various materials (e.g., metal, composite, polymer, and biological materials) [7][8][9][10][11][12][13][14][15][16][17][18][19]. Moreover, the method is being continuously developed and enlarging its application area [20][21][22]. Recently, the method has been applied to analyze the viscoelastic Poisson's ratio of solid propellants [23,24].…”
Section: Introductionmentioning
confidence: 99%